Portrait of BEYONDERS asinspiration towards biographic research (Biograficzne badania nad twórczością. Teoria i empiria, 2016)
The aim of this article is to present the concept of Paul E. Torrance that describes a transgressive portrait – beyonder as an example of individual existence that in an artistic way transcends itself and any external limitations. Understanding this new quality and style of “being beyond” enables finding a new perspective in looking at man’s biography.